In vivo evaluations of wound healing and anti microbial properties of tualang honey using a full thickness burn wound in sprague dawley rats - Sukur, Salmi Mohamed (2010)
The bum wound serves as a portal of entry for colonizing opportunistic microorganisms which can affect wound healing. The effect of Tualang honey on wound healing in the bacterial contaminated full-thickness bum wounds was evaluated in this study. The objectives of this study is to evaluate the wound contraction, antimicrobial properties and histological aspects of Tualang honey in treating full thickness bum wounds in a rat model in comparison to Chitosan gel or Aquacel-Ag®. The effect ofTualang honey on wound healing in the full-thickness bum wounds was evaluated in 36 male Sprague Dawley rats. The rats were randomly divided into 3 groups (n=l2/group). Rat were anesthetized, and three full thickness bum wounds were created on each rat using a modified metal screwdriver heated using flame from blow torch. Each group of rats was inoculated with a different organism in the bum wounds: Group A was inoculated with Pseudomonas aentginosa, Group B was inoculated with Klebsiella pneumoniae and Group C was inoculated with Acinetobacter baumanii. One wound on each rat was dressed with either Tualang honey, Chitosan gel or Aquacel-Ag®. The rats were subjected to the evaluation period of 3, 6, 7, 9, 12, 14, 15, 18 and 21 days, where the wow1d size, microbiological and histological findings were assessed. The results of this study revealed that the mean wound size of the Tualang honey-treated wounds was not statistically different than those of the Chitosan gel or Aquacel-Ag® treated wounds when the wounds were compared throughout the entire expetiment (P> 0.05). However, comparing the mean wound size on day 21 alone revealed that the Tualang honey-treated wounds were smaller in comparison to that of the Chitosan gel and Aquacel-Ag® treated groups. The quantitative and semi-quantitative methods showed that there was a significant reduction in The bum wound serves as a portal of entry for colonizing opportunistic microorganisms which can affect wound healing. The effect of Tualang honey on wound healing in the bacterial contaminated full-thickness bum wounds was evaluated in this study. The objectives of this study is to evaluate the wound contraction, antimicrobial properties and histological aspects of Tualang honey in treating full thickness bum wounds in a rat model in comparison to Chitosan gel or Aquacel-Ag®. The effect ofTualang honey on wound healing in the full-thickness bum wounds was evaluated in 36 male Sprague Dawley rats. The rats were randomly divided into 3 groups (n=l2/group). Rat were anesthetized, and three full thickness bum wounds were created on each rat using a modified metal screwdriver heated using flame from blow torch. Each group of rats was inoculated with a different organism in the bum wounds: Group A was inoculated with Pseudomonas aentginosa, Group B was inoculated with Klebsiella pneumoniae and Group C was inoculated with Acinetobacter baumanii. One wound on each rat was dressed with either Tualang honey, Chitosan gel or Aquacel-Ag®. The rats were subjected to the evaluation period of 3, 6, 7, 9, 12, 14, 15, 18 and 21 days, where the wow1d size, microbiological and histological findings were assessed. The results of this study revealed that the mean wound size of the Tualang honey-treated wounds was not statistically different than those of the Chitosan gel or Aquacel-Ag® treated wounds when the wounds were compared throughout the entire expetiment (P> 0.05). However, comparing the mean wound size on day 21 alone revealed that the Tualang honey-treated wounds were smaller in comparison to that of the Chitosan gel and Aquacel-Ag® treated groups. The quantitative and semi-quantitative methods showed that there was a significant reduction in bactetial growth in Tualang honey treated wounds compared to Chitosan gel and AquacelAg ® treated wounds in Group A and C. There was no statistically significant difference in the granulation tissue fonnation and epidennal thickness between the Tualang honey, Chitosan gel or Aquacel-Ag® treated wound when they were compared throughout the study. Nevertheless, early granulation tissue fonnation and epithelialization was seen in Tualang honey treated wounds by day 14 in bum wounds infected with Pseudomonas aeruginosa. In conclusions, clinical examination of the wounds and histological evaluation showed that Tualang honey gave the fastest rate of healing, the least inflammatory reaction and has most rapid neovascularisation compared with the other treatments. Tualang honey also provide good evidence of the effectiveness of the antibacterial activity of honey on burn wounds infected with Pseudomonas aeruginosa and Acinetobacter baumanii.